Promises and Challenges of Microalgal Antioxidant Production - Clementina Sansone; Christophe Brunet (Antioxidants, 2019)
The exploration of natural antioxidants for nutraceuticals and pharmaceuticals industries has recently increased. This communication aims to grasp the relevance of microalgae in the panorama of natural antioxidant molecules supply to industrial applications as alternatives and/or complements to those typically used from higher plants. Microalgal richness in antioxidant compounds and scavenging ability compared to higher plants is discussed in the context of microalgal biodiversity. We mainly focus on families of powerful antioxidant compounds that have been scarcely investigated in microalgae, such as phenolic compounds, sterols, or vitamins, discussing the promise and challenges of microalgae as providers of health benefits, for instance, through their use as functional food ingredients.